Phase-field modeling of interfacial debonding in multi-phase materials via an adaptive isogeometric-meshfree approach. (15th June 2022) - Li, Weidong; Nguyen-Thanh, Nhon; Zhou, Kun
Highlights: An adaptive isogeometric-meshfree approach is developed for the phase-field modeling of interfacial debonding in multi-phase materials. This approach introduces the convenient implementation of both the regularized interfacial energy and the regularized crack surface energy. This approach can efficiently simulate crack initiation, propagation, interfacial debonding and matrix cracking in multi-phase materials. Abstract: The phase-field modeling of fracture in multi-phase materials is conducted via an adaptive isogeometric-meshfree approach. In this modeling, the crack and interface phase fields are introduced for the regularized representations of crack surfaces and interfaces, respectively, and a convenient approach is proposed for implementing the regularized energy related to both crack surfaces and interfaces without requiring the line integration along them. Numerical implementations of the present modeling are performed via the isogeometric-meshfree approach that constructs the equivalence between isogeometric and meshfree approximations. The developed approach can conveniently achieve mesh refinement around interfaces or cracks, and dynamically track cracks without requiring crack propagation criteria. Moreover, behaviors including the crack initiation, propagation, coalescence, interfacial debonding and matrix cracking of multi-phase materials can be efficiently captured. Finally, simulations are conducted for analyzing two- and three-dimensional fracture of multi-phase materials to demonstrate the reliability of the developed approach.